AGGREGATION PROPERTIES OF BLOOD CELLS AND VASCULAR CONTROL OVER THEM IN PATIENTS WITH ARTERIAL HYPERTENSION AND DYSLIPIDEMIA - I. N. Medvedev; I. A. Skoryatina (Российский кардиологический журнал, 2015)
Aim. To find out the strength of blood cells aggregation properties and specifics of antiaggregation vascular control in persons with arterial hypertension and dyslipidemia.Material and methods. The study was done on 380 patients with arterial hypertension of 1 -2 grade, risk 4 with dyslipidemia lib type, of middle age. Controls were 26 healthy same aged people. Studies were done with biochemical, hematological and statistical methods.Results. Among the patients studied with arterial hypertension and dyslipidemia we found a decrease of antioxidant plasma protection with activation of lipid oxidation, that significantly stimulated blood cells and caused alteration of vessel wall. In the persons studied there was significant decrease of the control of vessel wall over the increased cells aggregability.Conclusion. In comorbidity of arterial hypertension with dyslipidemia there is excessive erythrocyte, thrombocyte and neutrophils aggregation with a decrease of antiaggregation control by vessel wall.